EXAMINING THE IMPACT OF WELL-BEING ORIENTED MANAGEMENT TOWARD KNOWLEDGE SHARING - Tegar Satya Putra (Jurnal Akuntansi Dan Manajemen, 2023)
This research paper aims to explore the relationship between knowledge sharing and well-being oriented management in organizations. Specifically, we investigate whether a well-being oriented management approach is positively associated with knowledge sharing behaviors among employees. Drawing on the literature on knowledge management and well-being, I propose a conceptual model that posits well-being oriented management as an antecedent of knowledge sharing behaviors. A survey of employees in various organizations is conducted to test our conceptual model. The results suggest that well-being oriented management is positively related to knowledge sharing bi-dimension, namely knowledge donating and knowledge giving. This finding supports the notion that when employees feel valued and supported in the workplace, they are more likely to share knowledge with their colleagues. We discuss the implications of our findings for managers and organizations interested in promoting knowledge sharing and employee well-being. The limitations of our study and suggest avenues for future research is also highlighted. Overall, this research contributes to the understanding of the role of well-being oriented management in promoting knowledge sharing behaviors in organizations, and provides insights for practitioners interested in creating a positive work environment that fosters knowledge sharing and employee well-being.